Single-layer graphene doping through molecular interaction: field-effect transistor and atomic force microscopy investigations. (May 2015) - Late, Dattatray J.
Abstract : The single-layer graphene has attracted considerable attention for the promising applications in new generation nanoelectronics and optoelectronics devices because of the high deal carrier mobility. Present investigations deal with the effect of chemical/molecular doping with varying the concentration of strong electron acceptor molecule such as tetracyanoethylene (TCNE) on transfer characteristics of single-layer graphene transistor. The Dirac point shift toward the positive gate voltage as a function of increasing concentration of TCNE molecules clearly indicates that the graphene is P -type doped. Our results indicate that the fermi energy level can be controlled by the amount of molecular doping in order to obtain graphene transistors with tunable Dirac points, which can be easily configured into functional nanoelectronic devices.